2022
DOI: 10.3389/fneur.2022.857402
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Immunotherapy as the Only Predictor of Secondary Generalization in Very-Late-Onset Myasthenia Gravis With Pure Ocular Onset

Abstract: During the past two decades, an increasing number of patients with very-late-onset myasthenia gravis (v-LOMG) with an onset age of 65 years or older have been identified. However, few studies explore the predictors of secondary generalization in patients with v-LOMG with pure ocular onset. In this retrospective cohort study, 69 patients with v-LOMG were divided into ocular MG (OMG) and generalized MG (GMG), and the clinical characteristics and outcomes were compared. Cox regression analysis was performed to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…19,30,31 Two studies included only older populations, such as 70 years or older 32 and 65 years or older. 33…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…19,30,31 Two studies included only older populations, such as 70 years or older 32 and 65 years or older. 33…”
Section: Resultsmentioning
confidence: 99%
“…21,23,27,36,47 Nine studies found no association with secondary generalization. 7,20,22,24,33,35,39,41,42 Six studies did not report on an analysis of association with SGMG. 19,26,32,44-46 Four studies did not report on the presence or absence of thymic abnormalities.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations